Exploring Selected Factors That Determine Graduation Times in an Undergraduate Programme - Ratnaweera, Manorika; Khareedi, Rohini (Asian Online Journals, 2021)
Introduction: Timely graduation is of colossal importance to students, universities, and other stakeholders. The purpose of this retrospective study was to examine the time taken to graduate and to determine if pre-enrolment demographic and experiential characteristics of students are predictive of the aggregate grade point average. The secondary purpose of the study was to identify individual aspects between cohorts based on the time taken to complete the course. Method: The sample for this study included all students enrolled in the Bachelor of Health Science (Oral Health) program at the Auckland University of Technology from 2008 to 2016. The desensitized data were subjected to descriptive and inferential statistical analysis. Results: The mean grade point average in the first year was lowest in the cohort that took five years to complete and highest in the cohort that took three years to complete. Each year’s grade point average was positively correlated to the next year’s grade point average. The level of prior education and work experience were predictive of the aggregate grade point average in those completing in three years (P<0.05) but not in those completing in four years (P>0.05) Conclusion: Pre-enrollment factors, level of prior education and work experience were predictive of aggregate grade point average in the cohort completing in three years but not in the cohort completing in four years.
Keywords: Predictors; Grade point average; Graduation